2001
DOI: 10.1152/ajprenal.2001.280.4.f706
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of juxtaglomerular NOS1 and COX-2 precedes glomerulosclerosis in fawn-hooded hypertensive rats

Abstract: This study describes elevated histochemical signals for nitric oxide synthase-1 (NOS1) and cyclooxygenase-2 (COX-2) in juxtaglomerular apparatus (JGA) and adjacent thick ascending limb of the kidney of fawn-hooded hypertensive rats (FHH). Two different age groups of FHH (8 and 16 wk; FHH8 and FHH16, respectively) were compared with genetically related fawn-hooded rats with normal blood pressure (FHL) that served as controls. Histopathological changes in FHH comprised focal segmental glomerulosclerosis (FSGS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
(62 reference statements)
4
28
0
Order By: Relevance
“…13,19 For immunohistochemistry, the following primary antibodies were used: (1) rabbit monoclonal antibody against an exon 2-encoded NOS1 domain (amino acids 1 to 181 from rat brain; Sigma), (2) rabbit polyclonal antibody against an exon 12 to 21-encoded NOS1 domain (Calbiochem), (3) goat polyclonal antibody against a C-terminal COX-2 peptide (Santa Cruz Biotechnology), and (4) rabbit polyclonal antibody against rat Tamm Horsfall protein (THP; against the whole protein; gift from J. Hoyer, Philadelphia). For detection, Cy3-coupled goat anti-rabbit or donkey anti-goat, and Cy2-coupled mouse anti-rabbit antisera were used (Dianova).…”
Section: Histochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…13,19 For immunohistochemistry, the following primary antibodies were used: (1) rabbit monoclonal antibody against an exon 2-encoded NOS1 domain (amino acids 1 to 181 from rat brain; Sigma), (2) rabbit polyclonal antibody against an exon 12 to 21-encoded NOS1 domain (Calbiochem), (3) goat polyclonal antibody against a C-terminal COX-2 peptide (Santa Cruz Biotechnology), and (4) rabbit polyclonal antibody against rat Tamm Horsfall protein (THP; against the whole protein; gift from J. Hoyer, Philadelphia). For detection, Cy3-coupled goat anti-rabbit or donkey anti-goat, and Cy2-coupled mouse anti-rabbit antisera were used (Dianova).…”
Section: Histochemistrymentioning
confidence: 99%
“…Standard incubation procedures were used as described. 13,19 In double-labeling experiments, suitable secondary antibodies coupled to different fluorochromes were applied. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative PCR studies indicated that Mxi1 and Rbm20 were differentially expressed in the renal vasculature of FHH and FHH.1BN congenic strain F. These data indicate that transfer of this 2.4-Mbp region from BN to FHH rats restores the myogenic response of AF-art and autoregulation of RBF, decreases K ϩ current, and slows the progression of proteinuria and renal injury. kidney; glomerulosclerosis; chronic renal failure; renal hemodynamics THE FAWN-HOODED HYPERTENSIVE (FHH) rat is a genetic model of hypertension (33) that develops proteinuria, glomerulosclerosis (21,30,37,47), and chronic kidney disease (22,(25)(26)(41)(42). We have previously reported that the development of proteinuria and glomerular injury in FHH rats is associated with an impaired autoregulation of renal blood flow (RBF), glomerular filtration rate (GFR), and glomerular capillary pressure (Pgc) (24,40,43,48).…”
mentioning
confidence: 99%